Pengaruh biaya lingkungan, green innovation dan keputusan investasi terhadap nilai perusahaan dengan profitabilitas sebagai pemoderasi - Prakoso, Sawung; Zulfiati, Lies (Jurnal STEI Ekonomi, 2024)
This research aims to examine the impact of environmental impacts, green innovation and investment decisions on company value with moderation through profitability. This research for shows that environmental costs have no effect on company value in mining sector companies in Indonesia in 2019-2022, green innovation has an effect on company value in mining sector companies in Indonesia in 2019-2022, investment decisions have no effect on company value in mining sector companies in Indonesia in 2019-2022. Furthermore, profitability moderates environmental costs and influences company value in mining sector companies in Indonesia in 2019-2022. Profitability moderates the effect of green innovation on company value in mining sector companies in Indonesia in 2019-2022. profitability moderates investment decisions and has no effect on company value in mining sector companies in Indonesia in 2019-2022 with company value can be explained by environmental costs, green innovation, investment decisions and profitability. Article Information: Received 2/13/2024 / Revised 4/26/2024 / Accepted 5/16/2024 / Online First 5/17/2024